LEGAL ASPECTS OF MERGER STUDY ON PT BANK TABUNGAN PENSIUNAN NASIONAL TBK - Jesslyn, Jesslyn (Penerbit Universitas Atma Jaya Yogyakarta, 2021)
Mergers and acquisitions have been the driving force of the world economy and have played an important role in the strategies of many companies. To create a healthy, strong, and competitive banking structure, several steps are needed to consolidate banking sector. To realize this vision, Financial Services Authority (OJK) encourages investors and the banking industry to consolidate, including through a merger, one of those is the Merger of BTPN and SMBCI. The purpose of this article is to examine legal aspects in the merger process and procedure as well as the main issues relating to the application of principles in the protection of employees and minority shareholders. The method used to address the problems in this article is normative legal research, which shows that the merger is a horizontal merger by applying the principles of fair dealing and appraisal rights and not forgetting to apply the principle of employee protection.